2011
DOI: 10.2217/pme.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Concerning Pharmacogenomics Among Healthcare Professionals

Abstract: Pharmacogenomics has become an area of great potential in the medical community. Therefore, the assessment of the knowledge and attitudes among healthcare professionals is essential. The purpose of this systematic literature review is to explore the knowledge and attitudes of healthcare professionals regarding pharmacogenetic testing with a specific emphasis in oncology. A total of 12 articles were found and reviewed. A majority of the articles reported only on the attitudes of healthcare professionals. Four o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Advances in the science and practice of pharmacogenomics could outpace the preparedness and receptivity of physicians and other clinical staff to effectively use the results to tailor therapy. Genomic medicine features a complex knowledgebase that is unfamiliar to both patients and physicians, many of whom have had no formal training on these concepts [15–18]. Given the complexity of the reporting and interpretation, integrating pharmacogenomics results in the electronic health record may lead to difficulty with understanding the clinical significance or problems in applying results toward individual patient cases [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the science and practice of pharmacogenomics could outpace the preparedness and receptivity of physicians and other clinical staff to effectively use the results to tailor therapy. Genomic medicine features a complex knowledgebase that is unfamiliar to both patients and physicians, many of whom have had no formal training on these concepts [15–18]. Given the complexity of the reporting and interpretation, integrating pharmacogenomics results in the electronic health record may lead to difficulty with understanding the clinical significance or problems in applying results toward individual patient cases [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenomics, a class of predisposition genetic testing for drug response, is new to many physicians in general and focuses on ‘how individual genetic differences affect drug response' [50]. A review of the literature found that 5 of 6 studies completed determined that physicians felt that they had limited knowledge of pharmacogenetics [51]. This is also true for medications created for specific genotypes which also received a low rating.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a pharmacogenomics outreach program offered by a large national pharmacy benefit manager, less than 1% of physicians contacted for facilitation of a genetic test to inform clopidogrel use already ordered or were planning to order a test despite a black box warning from the FDA on the risk for subsequent cardio vascular events for CYP2C19 poor metabolizers (unpublished results of a pilot program within a national Pharmacy Benefit Manager that operates by facilitating a CYP2C19 genetic test in clinically appropriate cases after an intial prescription for clopidogrel [ Examining this disconnect between the clinical literature and the evidence-based use of molecular tests, it has been suggested that the lack of education and training in healthcare workers prevents widespread adoption [39,40]. In the example of warfarin, a very time sensitive test, robust adoption of testing simply cannot ensue when two-thirds of anticoagulant prescribers express that they have a general lack of knowledge regarding pharmacogenomic testing [41].…”
Section: Opportunities To Improve Adoption Of Personalized Medicinementioning
confidence: 99%
“…Compounding this lack of education is a fear of the ethical concerns of pharmacogenomic testing. A recent literature review suggested that ethical concerns about the fear of discrimination, lack of privacy and the need for informed consent still persist [39]. There are certainly thoughtful ways to address these concerns while still promoting patient's access to clinically valuable diagnostics.…”
Section: Opportunities To Improve Adoption Of Personalized Medicinementioning
confidence: 99%